THE EFFECT OF VISUAL MEDIA ON STUDENTS’ WRITING EXPLANATION TEXT ABILITY AT ELEVENTH GRADE SMA NEGERI 1 SIABU 2017/2018 ACADEMIC YEAR - sarah mutiara aritonang (JURNAL LINER (Language Intelligence and Educational Research), 2018)
The purpose of this research are to find out: 1) the application of visual media on students’ writing explanation text ability at eleventh grade SMA Negeri 1 Siabu. 2) The students’ writing explanation text before and after using visual media at the eleventh grade of SMA Negeri 1 Siabu. 3) The significant effect of visual media on the students’ writing explanation text at the eleventh grade of SMA Negeri 1 Siabu. Method of the research is experimental. The population of this research are all of the eleventh grade students of SMA Negeri 1 Siabu that consist of 171 students. Purposive sampling technique is uses to get the sample of research consist of 31 students. The technique for collecting data are observation sheet and test. The result mean score of the application of visual media is 3.3 categorized “Very Good”. Before using Visual Media is 50. 4 categorized “Low”. Meanwhile, after using Visual Media is 73.8 categorized “Good”. The result of ttest 14.72 and ttable 2.04 it means that there is any significant effect of using Visual Media on students’ writing explanation text ability at eleventh grade SMA Negeri 1 Siabu 2017/2018 Academic Year.